(3eSGFd abgjI YOjOIs - (3MSjf Hf YHO GdUeO Hf eMeO GdLHYj (B((3HVe aaJM(B) (3GdYGedj GdMGQKj GdgeOGfqj,J (B984 (3g` s
(3ChdgG (B:s
(3hHYO abO jNai Ydi Phi dJMbjb eSGFd YOjOI abgjg s
(3BNQgG (B:s
(3hPdc eY Vjb GdeLGd hJTJJ GdHGd JeJ GdQSGdI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH(B18s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B240 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B17s
(3eUOQ GbJfGA GdCUd (B:s
(3BjI Gddg GdMcje GdYGeI (B_ (3GdfLa (B(369) s
Keywords: (3GdeLGejYs